A Q-switched multi-wavelength Brillouin erbium fiber laser with a single-walled carbon nanotube saturable absorber - Tan, S.J.; Harun, Sulaiman Wadi; Ahmad, F.; Nor, Roslan Md; Zulkepely, N.R.; Ahmad, Harith (IOP Publishing, 2013)
A Q-switched multi-wavelength Brillouin erbium fiber laser (MWBEFL) is demonstrated using a single-walled carbon nanotube-polyethylene oxide (SWCNT-PEO) saturable absorber (SA). The SA is fabricated by cutting off a small part of the developed SWCNT-PEO film and sandwiching it in between two FC/PC (fiber connector/physical contact) fiber connectors. Multi-wavelength combs with ten lasing lines and spacing of 0.158 nm are obtained by the use of 2 km long dispersion compensating fiber as the Brillouin gain medium and a four-port circulator to isolate and circulate the odd-order Stokes signals. Q-switched pulse trains with a repetition rate of 105.2 kHz and a pulse width of 0:996 μs are obtained in the proposed MWBEFL at a 1480 nm pump power of 120 mW and a Brillouin pump power of 5.4 dBm.